Teachers' Efforts in Developing Aqidah and Akhlak Learning through Social Projects (Upaya Guru dalam Mengembangkan Pembelajaran Akidah Akhlak melalui Social Project) - Ridho, Ahmad; Al Farabi, Mohammad (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study aims to describe the teacher's efforts in developing Akidah Akhlak learning through the social project learning model in class IX of Madrasah Tsanawiyah (MTs) Al Washliyah Sei Lumut. This research uses a qualitative method with descriptive analysis. The research informants were Akidah Akhlak teachers, students, and the local community. Data collection techniques were carried out through observation, interviews, and document studies. The results showed that the teacher's effort to develop Akidah Akhlak learning was with the ‘Clean Friday’ activity. This activity has a huge impact and provides a positive commitment to building character and improving the quality of students. Through this effort, teachers have realized character building, improved interaction skills, and contributed to social activities in the community.Keywords: Teacher Efforts, Akidah Akhlak Learning, Social Project